Islands Philippines - The Travel Preview System (Houston, Tex. Travelview International, 1996)
Features the three major islands : Luzon, Visayas and Mindanao. Describes Philippines where the Pacific Ocean meets the South China Sea.
Title on container: Philippines : the beginning of a great vacation.
VHS.
Keywords: Philippines -- Description and travel